Representations of facial expressions since Darwin. (28th April 2022) - Perrett, David
Abstract: Abstract: Darwin's book on expressions of emotion was one of the first publications to include photographs (Darwin, The expression of the emotions in Man and animals, 1872). The inclusion of expression photographs meant that readers could form their own opinions and could, like Darwin, survey others for their interpretations. As such, the images provided an evidence base and an 'open source'. Since Darwin, increases in the representativeness and realism of emotional expressions have come from the use of composite images, colour, multiple views and dynamic displays. Research on understanding emotional expressions has been aided by the use of computer graphics to interpolate parametrically between different expressions and to extrapolate exaggerations. This review tracks the developments in how emotions are illustrated and studied and considers where to go next.